Membangun Harmoni: Perbandingan Budaya Damai di Berbagai Tingkat Kelas SMA Laboratorium Percontohan UPI di Kota Bandung - Elfitra Khairin Lutfiah Br. Sitepu; Nandang Budiman; Sardin Sardin (Departement of Mathematics Education, 2024)
This study aims to determine the comparison of the culture of peace in classes X, XI, and XII at UPI Pilot Laboratory High School. The research method used descriptive statistics with a quantitative approach. The measuring instrument used is the culture of peace scale. The sample of this study amounted to 75 students from classes X, XI, and XII. Based on the results of the research analysis, the Kruskal-wallis value is 0.400 and sig = 0.819 > α 0.05. This indicates that Ho is accepted, which means there is no significant difference in the culture of peace scores in classes X, XI, and XII. The average score of culture of peace for males is highest in class X, and the average score of culture of peace for females is highest in class XII.